EFEKTIVITAS BERBAGAI KONSENTRASI PUPUK CAIR URINE SAPI PADA PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA (Brassica Oleracea var. Botrytis L.) - Nur Hafizah; Anita Anita (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
Cabbage Flowers is one of the vegetable crops that have high commercial value and prospects in Indonesia, because these plants have a central role as meeting the needs of food, feed and the domestic industry. To improve the quality and yield of couliflower are some things to consider include the supply of nitrients to the plants throug fertilization, one cow urine as an organic liquid fertilizer as solutions and alternatives to obtain optimal results in podsolic land. This study aims to determine the concentration of liquid fertilizer of cow urine on the growht and yield of couliflower. The research was conducted from March to June 2017, housed in the Village Hariang Banua Lawas Distric of Tabalong. The study was conducted using a Randomized Block Design (RBD) with a single faktor consisting of 6 level with 4 group. Faktor to be examined is the concentration of liquid fertilizer of cow urine consists of : : 5 cc.l-1 (u1), 10 cc.l-1 (u2), 15 cc.l-1 (u3), 20 cc.l-1 (u4), 25 cc.l-1 (u5), dan 30 cc.l-1 (u6). The results showed liquid fertilizer of cow urine with various concentration has no effect on the observed variables that plant height, leaf number, age of the plant during flowering, severe fresh crop planting and perimeter planting flowers.